Diagnóstico da Rede Sociotécnica de Inovação em uma Instituição Federal de Ensino Superior - Silva, Daniela Salgado Gonçalves da (2018)
Innovative activity is considered a social and collective process, in which its learning takes place through interactions. The more complex the learning, the greater the need for interaction and complementarity. Therefore, there is an open interaction environment that depends on the communities and networks of innovation that should create value and bring collective benefits. In this sense, the present research aims to diagnose the articulation existing in the strategic sectors formed by a sociotechnical network linked to the management of innovation in a São Paulos’s state Federal University and, to identify with the sector representatives, which strategies could be implemented to increase the effectiveness of the processes managed by this network. It is a qualitative-quantitative research whose strategy is the case study by means of the inductive method, where an empirical investigation was carried out that contemplated evaluating a contemporary phenomenon within its real context. As a time cut for data collection, we have the period between the second half of 2016 and the first half of 2018, with a view to identifying which are the institutional networks, how they flow from the perception of the sector representatives, and what results can we from the perceptions identified in the interviewees' statements. As for the use of results, this is an applied research whose practical emphasis is on problem solving. As for the ends, it is a descriptive research. As for the nature of the method, it is a qualitative-quantitative research. The case unit is a governmental organization, part of the apparatus of the State, from the public management, non-profitable character with type of academic organization: University. The current reality of the structure linked to the management of innovation of this institution is seen in this research as the central problem. This work aimed to describe, analyze and identify the degree of sector interaction and level of articulation of this sociotechnical network of research and innovation management based on the following question: "Considering the social responsibility of a federal university in the interior of the state of São Paulo, to what extent does the political and administrative articulation of the sociotechnical network for innovation management occur, since there is a potential possibility of sectoral integration that has a positive impact on institutional management?" This research is justified by the importance of the Scientific, Technological and Innovation Institutions (STII), including public institutions of higher education, in mapping processes with the establishment of an articulated network in which to better organize their scientific capital, financial and human resources expended in the aggregate of a considerable burden of bureaucratic, academic, research and financial activities. The assumptions of the study consider that the articulation between the actors of this network is deficient and that, due to the constant movement of the unstable political scene, as well as of the updates in the legislation related to science, technology and innovation, the university starts to implement organizational arrangements for to meet the requirements of the federal government and to meet the requirement of social responsibility, but not necessarily promoting integration in its entirety among the strategic sectors. At the end of this research, we were able to identify the perception of the representatives of the analyzed organizational units and to point out strategic elements that which aim to contribute to the public management of this institution. The result contributed to generating a suggestion of articulation and strategic sector interaction in this organization, in order to foster the management of innovation, based on the current reality, a new administrative and political team that assumed its functions for the 2017- 2020.